Prognostic Value of Vimentin Is Associated With Immunosuppression in Metastatic Renal Cell Carcinoma - Yao, Jia xi; Chen, Xiang; Zhu, Yan jun; Wang, Hang; Hu, Xiao yi; Guo, Jian ming (Frontiers in Oncology, 2020)
Introduction: Vimentin, a classical marker of epithelial-mesenchymal transition, reflects the invasiveness of cancer cells. Its role in the genesis and progression of tumor has been reported in various cancers, including renal cell carcinoma. However, the impact of vimentin on tumor microenvironment, particularly it’s implication with tumor infiltrating immune cells, is unknown. Methods: We conducted this study in 231 patients with metastatic renal cell carcinoma (mRCC) to determine the potential relationship between vimentin and immune status. Using immunohistochemical staining, expression of vimentin, CD8, FOXP3, PD-1, and PD-L1 were evaluated in resected tumor tissue. Kaplan-Meier analysis and Cox regression models were used for survival analysis. Chi square test, fisher’s exact test, and Mann–Whitney U test was used for comparison between vimentin high and low groups. Results: High expression of vimentin, sPD-L1, and PD-1 indicated poor overall survival, while low Treg or high CD8+ T cells infiltration indicated long overall survival. Stroma PD-L1 (P=0.030), vimentin (P=0.026) expression, and CD8+ T cell infiltration (P<0.001) were independent prognostic factors in mRCC. High vimentin expression was accompanied with high PD-1, PD-L1 expression and increased Treg infiltration (all P<0.001), indicating immunosuppression in tumor microenvironment. Conclusions: We revealed that vimentin expression was associated with immunosuppression in mRCC, and the immune-suppressive status might be possibly posed by PD-1/PD-L1. Patients with high vimentin expression may acquire potential benefit from the recently approved PD-1/PD-L1 inhibitors. However, further clinical trials are needed to validate our findings.